MODALITAS Kí–NNEN DALAM KALIMAT BAHASA JERMAN - Triyono, Sulis (Diksi, 2007)
This article is an introduction to the basic concept of using the modality ofk nnen 'can' in German sentences. The k nnen unit of modality functions to revealthe speaker's attitude and has the status of a verb modifier. Modality is divided infunction by some linguists into different areas like epistemic modality, modalitymarkingadverb, and deciderative and optative mode devices.On the basis of the results of a study conducted, it could be concluded thatthe modality unit of kí¶nnen 'can' in a sentence in German has the characteristics asfollows: (1) it is merely an attributive element in a verb phrase rather than a coreone so that if deleted the sentence remains grammatical, (2) its relation to any otherelement is loose in nature, and (3) its position is so firm that it cannot be permutatedwith any other element in a sentence. In addition, in sentences the kí¶nnen modalityvaries in meaning according to sentence context. The meaning expressed by thekí¶nnen modality can be of possibility, ability, or permission.Keywords: the kí¶nnen modality